El agresor del delito de violencia intrafamiliar y su tratamiento psicológico como medida alternativa de solución de conflictos - Aguilar Rodríguez, Luis Fernando (2019)
In the present research project prior to obtain the Lawyer degree, named “The aggressor of the crime of intrafamily violence and its psychological treatment as an alternative measure of conflicts resolutions” carried out in the south of Guayaquil, Guayas province, articularly in the Valdivia Sur area, where it was possible to clearly demonstrate the intrafamily violence problems that arise daily and how it is yet not possible to reduce this serious social problem. It is necessary to emphasize that there is joint work among the authorities to reduce the rate of intrafamily violence cases; however, the results are not favorable, since there is an increase and recidivism of these cases. We can find in this investigation that the types of violence that are the most demanded are psychological violence and physical violence, which is one of the most quiet and dangerous aggression that affects our society. In Ecuador, since 2014, was established for the first time the aggressor who commits psychological violence within the Organic Penal Code (COIP), the penalty is administered depending on three levels of affectation, which can be mild, moderate and severe, where the aggressor can be sentenced from 30 days to 36 months in prison. Domestic violence is a permanent problem that affects families, regardless of economic capacity, age and place of residence…………